Smart Ordering System via Bluetooth - Hashim, Nik Mohd Zarifie; Ali, Nur Alisa; Ja'afar, Abd Shukur; Mohamad, Najmiah Radiah; Salahuddin, Lizawati; Ishak, Noor Asryran (IJCTT, 2013)
Conventional method that usually been used in restaurant is by taking the customer’s orders and write it down on a piece of paper. Many ordering system have been proposed in order to undertake this issue. The project is proposed with the Bluetooth technology as the communication medium and Peripheral Interface Controller (PIC) as the hardware which implements faster ordering system. It consists of a keypad at customer’s table as a remote control and monitor at kitchen or counter to display the ordering information systematically. The aim for this project is to build and design both hardware and software for the ordering and delivering system at restaurants by using keypad, display screen via Bluetooth communication. The project also targeted to receive information that works around 100m away with the specific location. Result shows that the hardware and software are successfully functional and able to be used as a smart ordering system. The project was able to solve the lack number of the worker, reduce the lateness and the error on ordering foods by the customers. For the future target, using touch screen display and compress the device to more compact device are recommended as the nowadays demand to interact young generation for using this system.